Beginning BBC micro:bit A Practical Introduction to micro:bit Development - Seneviratne, Pradeeka (Apress, 2018)
Learn essential concepts and techniques to build simple-to-advanced projects and overcome common programming challenges in micro:bit development. Beginning BBC micro:bit will take you through the complete features and capabilities of the micro:bit controller, enabling you to program and build your own projects. The uses are endless for the micro:bit and this books will help get you started on building your next project with this popular and easy-to-use microcontroller. You'll use online Python Editor and Mu Editor to build your own applications. Reviewed by the micro:bit developer team, this comprehensive guide also provides clean code examples to help you learn the key concepts behind the micro:bit API. .